Alcohol and its relationship to offence variables in a cohort of offenders with intellectual disability. (December 2013) - Lindsay, William R.; Carson, Derek; Holland, Anthony J.; Taylor, John L.; O'Brien, Gregory; Wheeler, Jessica R.; Steptoe, Lesley
Abstract Background Alcohol use and misuse may be lower in people with intellectual disability (ID) than in the general population but may be related to offending. Method Alcohol-related crime and history of alcohol use was recorded in 477 participants with ID referred to forensic ID services and related to offending. Results Level of alcohol-related crime and history of alcohol misuse was lower than in some previous studies at 5.9% and 20.8%, respectively. History of alcohol abuse was associated with alcohol-related offences and theft. Higher rates of alcohol problem history were associated with histories of a number of offences, psychiatric disturbance in adulthood, psychiatric disturbance in childhood, and experiences of childhood adversity. Most effect sizes were weak or moderate. Conclusions The convergence of childhood adversity, psychiatric problems in childhood and adulthood, and alcohol abuse is consistent with studies that have found these as risk markers for offending.